The Description of the Impact of the Covid-19 Pandemic on MSME: Some Fall, Some Prevail - Sri Palupi Prabandari, Sri Palupi Prabandari (AFEBI Economic and Finance Review, 2021)
The significant drop on the number of customers due to the Covid-19 pandemic has led micro, small, and medium-sized enterprises into difficult days. The decline of customer’s purchasing power was caused by multiple problems. As people’s aggregate income decreases, the major-scale social distancing aimed at minimizing the virus spread hinders the ongoing business activities. This study aims to see the real condition of micro, small, and medium-sized enterprises amidst the pandemic from the aspects of finance, human resource, human resource’s welfare, and the business’ sustainability.